Attentional control of emotional interference in children with ADHD and typically developing children: An emotional N-back study. (August 2017) - Villemonteix, Thomas; Marx, Ivo; Septier, Mathilde; Berger, Christoph; Hacker, Thomas; Bahadori, Sara; Acquaviva, Eric; Massat, Isabelle
Abstract: Emotional interference control refers to the ability to remain focused on goal-oriented processes when confronted with disrupting but irrelevant emotional stimuli, a process that may be impaired in children and adults with attention deficit/hyperactivity disorder (ADHD). However, emotional interference levels are known to be associated with trait anxiety, and patients with ADHD often display elevated levels of trait anxiety, such as these may have confounded previous findings of decreased emotional interference control in this population. In the present study, male and female 8–13 years old (mean =11.0 years) children with ADHD (n=33) and typically developing (TD) children ( n =24) performed a visual emotional working memory (n-back) task with 2 memory loads and three different background pictures (neutral/positive/negative), and trait anxiety measures were obtained. Children with ADHD performed less well, and displayed increased emotional interference in the presence of aversive distractors when compared with TD children. Contrary to our expectations, trait anxiety did not mediate the association between diagnostic group membership and the degree of emotional interference control; however, co-morbid ODD was associated with decreased levels of emotional interference in ADHD. Future research should aim at characterizing the mechanisms subtending decreased emotional interference control in the ADHD population. Highlights: We used an emotional n-back paradigm to investigate emotional interference control in ADHD. Children with ADHD displayed increased emotional interference levels. Trait anxiety did not mediate the association between diagnosis and emotional interference scores. Comorbid ODD was associated with reduced emotional interference levels.